ASEAN's half century a political history of the Association of Southeast Asian Nations - Weatherbee, Donald E. (Rowman & Littlefield, 2019)
"Offers a critical analysis of the conventional wisdom regarding ASEAN and its efforts to transform Southeast Asia's security environment"--